Role of Autophagy in the Maintenance of Stemness in Adult Stem Cells: A Disease-Relevant Mechanism of Action - Chen, Shanshan; Wang, Wenqi; Tan, Hor-Yue; Lu, Yuanjun; Li, Zhiping; Qu, Yidi; Wang, Ning; Wang, Di (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an intracellular scavenging mechanism induced to eliminate damaged, denatured, or senescent macromolecular substances and organelles in the body. The regulation of autophagy plays essential roles in the processes of cellular homeostasis and senescence. Dysregulated autophagy is a common feature of several human diseases, including cancers and neurodegenerative disorders. The initiation and development of these disorders have been shown to be associated with the maintenance of disease-specific stem cell compartments. In this review, we summarize recent advances in our understanding of the role of autophagy in the maintenance of stemness. Specifically, we focus on the intersection between autophagy and adult stem cells in the initiation and progression of specific diseases. Accordingly, this review highlights the role of autophagy in stemness maintenance from the perspective of disease-associated mechanisms, which may be fundamental to our understanding of the pathogeneses of human diseases and the development of effective therapies.